Investigating mathematics teachers’ changes in practice during a professional development initiative - Guimarães, Rita Santos (2019)
The constant educational reforms, pedagogical innovations, and new technologies place teachers capacity for change as a necessary attribute to the profession. Professional development initiatives (PDI) have been tackling this issue with some success and research is now able to provide features that foster an effective intervention. However, many studies focus on PDI to implement reform, and not on change motivated by local school-based issues. The focus on reform might cloud essential features influencing teacher change and relationships between them for instance, the PDI are usually mandatory, top-down and neglect local characteristics of teachers and students. Therefore, the existing theoretical frameworks for teacher change developed based on these PDI are partial at best. This thesis reports on a study which investigated change in mathematics teachers’ practice with low achieving students. Acknowledging the complexity of teacher change in classroom practice, I sustained a long period of data collection to investigate change of three mathematics teachers. The overarching research question was: How do secondary mathematics teachers change within the context of a professional development initiative to innovate in their classroom practices? I developed and run a PDI to discuss lesson plans about fractions focused on visual representations. Over the period of one year, the teachers in a secondary school in England chose one low-set group to teach these collectively planned lessons. Before the new lessons began, I was already observing their regular lessons, and we were having meetings to discuss the initial ideas for the lesson plans. These allowed us to align our goals regarding the new approach the teachers were going to use during the collectively planned lessons. The nature of the study was exploratory, and the data collection methods reflected this stance: semi-structured interviews (3 with each teacher), informal conversations, many lesson observations (more than 250 hours), and 8 meetings with the teachers. The prolonged period with the teachers allowed me to build trust and rapport with the participants, which contributed to the in-depth view of the process of change and the influences affecting it, adopting a close-to-practice approach to research. Data from the lesson observations also allowed me to identify changes in practice during the project lessons for all the three teachers. I analysed the interviews, the notes from informal conversations and the meetings using grounded-theory techniques (Strauss and Corbin, 1998). The categories developed lead me to suggest influences affecting participants change coming from the PDI and the teachers' professional characteristics. I was also able to build explanations using the data that indicated how these influences were related to and building on to each other. The major finding of this study is a set of components that influenced the teachers participating in my research to change their classroom practices. More importantly than the set itself, my findings include a thorough discussion of the relationships between them and how they influenced the process of change. This set is divided into three parts. An initial part apparently neglected in other studies, is composed of the teachers' professional characteristics: ‘commitment to the job’, ‘curiosity’ and ‘classroom management’. These characteristics are important to maintain teachers' engagement with the project, but also as initial requisite so teachers can begin implementing changes in practice. The second part is the cycle of experimentation of the change process, and it is formed by a sequence of ‘follow the lesson plan’ and have a ‘positive experience’, these are mentioned in many studies about teacher change, and it also revealed as relevant in mine. The third and final part are features of the PDI, namely: ‘time’, ‘trust’, ‘support’, ‘familiarity’, ‘congruence’, ‘discussion’, ‘reflection’, ‘consistency’, and ‘agency’. Some of these features were embedded in the PDI design, and others emerged from my role in the project. Lastly, as a practical implication of my findings, I suggest the role of school-based designer, a person in the mathematics department with a role focused on supporting teachers and designing materials to tackle local problems within the school.